1996
DOI: 10.1088/0022-3727/29/5/039
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic observations of photon emissions in n-MOSFETs in the saturation region

Abstract: Direct spectrally resolved observations were made of the photon emissions n-channel MOSFETs biased in the saturation region. It was found that the total photon emission intensity measured in the range 1.45 - 2.75 eV is proportional to the substrate current and the correlation is independent of the bias condition, channel current and channel length. However, it was also found that the relationship between emission intensity at the low end of the range of energies varied with whereas the emission intensity at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In Ref. [26], the spectral characteristics of the emitted photons from n-channel MOSFETs biased into saturation were investigated directly using photon emission spectroscopy; the correlation between the substrate current of the bias voltages, channel current, and channel length were presented; theoretical calculation of the photon emission intensity based on the Bremsstrahlung radiation mechanism does not agree well with the experimental measurements when the variation of the channel electric field with bias was accounted for; this suggests that Bremsstrahlung radiation of hot electrons in the Coulomb-scattering field of the dopant atoms is unlikely to be the dominant mechanism of photon emission in n-channel MOSFETs; other mechanisms such as direct and phonon-assisted conduction-to-conduction band transitions have to be considered to explain the hot-carrier-induced photon emission mechanism.…”
Section: Inter-band Transitionmentioning
confidence: 99%
“…In Ref. [26], the spectral characteristics of the emitted photons from n-channel MOSFETs biased into saturation were investigated directly using photon emission spectroscopy; the correlation between the substrate current of the bias voltages, channel current, and channel length were presented; theoretical calculation of the photon emission intensity based on the Bremsstrahlung radiation mechanism does not agree well with the experimental measurements when the variation of the channel electric field with bias was accounted for; this suggests that Bremsstrahlung radiation of hot electrons in the Coulomb-scattering field of the dopant atoms is unlikely to be the dominant mechanism of photon emission in n-channel MOSFETs; other mechanisms such as direct and phonon-assisted conduction-to-conduction band transitions have to be considered to explain the hot-carrier-induced photon emission mechanism.…”
Section: Inter-band Transitionmentioning
confidence: 99%
“…Because the theoretical calculation based on the bremsstrahlung mechanism does not agree well with the experimental results when the variation of the channel electric field with bias is taken into account, Tao et al 19 concluded that the bremsstrahlung of hot electrons in Columbic field is unlikely to be the dominant mechanism of photonic emission in n-channel MOSFETs. Akil et al 20 did mention bremsstrahlung as one possible mechanism, but covering only a very small region of the emission spectrum.…”
Section: Theorymentioning
confidence: 99%
“…It has been established that MOSFETs emit light when biased at saturation [3][4][5][6][7][8][9][10]. The photon energy distribution can provide information on the energy levels involved in the carrier recombination mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The photon energy distribution can provide information on the energy levels involved in the carrier recombination mechanisms. Most of the work done so far has been in the visible wavelength range where the energy transitions of the carriers are higher than the Si bandgap [3][4][5][6]. Recently, publications have reported spectra from MOSFETs in the near-infrared (NIR) wavelength range where the energy transitions of the carriers are lower than the Si bandgap and involve intraband transitions of carriers [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%